The Trade Of Indonesian Spice Comodities In International Market - Herdiana Anggrasari; Jangkung Handoyo Mulyo (Agro Ekonomi, 2019)
This research is aimed to (1) observe the trade patterns and domination export in the spice commodities between Indonesia in international market and the countries as its main trade partners, and (2) observe the performance of the export and import in industry of Indonesia spices with its trade partner countries. Grubel-Lloyd Index (GLI) were used to detect whether the trade patterns in spice industry is as intra-industry or as inter-industry as well as to figure out the domination of the spice commodity export of Indonesia to its trade partner countries. The performance of the export and import in spice industry could be analyzed using the share of export and import between Indonesia and its trade partner countries. This research used the secondary data obtained from UNComtrade in a 15-year period (2002-2016) by concerning with a number of the main trade partner countries. The results of the research showed that the trade of Indonesian spice commodities in international market and among its main trade partners is categorized as a partial industry. Indonesia overall dominates the spice trade with its main trading partners; thus, the trade balance of Indonesian spice commodities is surplus. It is only with China and India in which the trade pattern is categorized as the intra-industry. Government needs to do some various efforts to encourage the increase of exports of Indonesian spices in the international market by developing market intelligence, enhancing the role of attachés in the spice trade diplomacy in the partner countries and potential countries.